Pedagogical Model for Environmental Education: Development and Validation in the Bachelor’s Degree in Education (Pedagogy and Psychology) - Hernández Abstengo, Damaris de la Caridad; Martínez Ferrer, Maydel; León Hernández, Miguel Alejandro (Journal of Education and Learning Environments, 2026)
The Bachelor’s degree in Education (Pedagogy and Psychology) trains a professional who, once graduated, will work as a school educational psychologist. Among their professional functions, they will provide educational guidance and counseling. Included in the content of these functions is environmental education; however, there are no subjects in the curriculum that address this content. Therefore, this study proposes a Pedagogical Model for environmental training in the Bachelor’s degree in Education (Pedagogy and Psychology). The methodology used is a systematization organized in cycles. Theoretical-level methods include: historical-logical analysis, analytical-synthetic, inductive-deductive, systemic-structural, from abstract to concrete, modeling, and systematization. At the empirical level, the methods used were: document analysis, surveys, observation, researcher’s diary, in-depth sessions, photography, source triangulation, and expert criteria. The proposal takes into account characteristics and principles, and is organized into the diagnostic subsystems, components of the pedagogical process, organizational components of the training process, and evaluation. Contents are proposed for the environmental education of students. It is concluded that the model is a theoretical construction that simplifies the most general elements that distinguish environmental education by considering the object of the profession and modes of action as basic cores. It has a systemic character given by the interrelation between the different subsystems and the components that comprise it, which determines that environmental education is the result of the system as a whole. It constitutes a tool for the work of the program that guides actions to develop knowledge, skills, and values.